2004
DOI: 10.1023/b:bebm.0000038167.45620.f3
|View full text |Cite
|
Sign up to set email alerts
|

Structural Organization of the Basal Layer and Morphofunctional Characteristics of Mouse Epidermal Cambial Cells

Abstract: The basal layer of mouse skin epidermis consists of special structures - rosettes functionally arranged in zones including about 20 rosettes. The rosette contains a central cambial cell; after division of this cell the mother cell remains in the center of the rosette and the daughter cell migrated to the center of a free rosette. The mother and daughter cells are dipole cells (sources of electric field). If the disposition of mother cells is unidirectional and they predominate over daughter cells, the latter c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…We previously found that cells in the epithelial tissue are grouped in rosettes with 6-7 cells at the periphery and 3-4 in the center [4,5,7]. Rosettes, in turn, are united in morphofunctional zones (about 24 rosettes per zone, a total of 240-250 cells) formed from cambial cells of the same type and presenting a cell base of the system regulating proliferation and differentiation processes in the epithelium [4,5].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We previously found that cells in the epithelial tissue are grouped in rosettes with 6-7 cells at the periphery and 3-4 in the center [4,5,7]. Rosettes, in turn, are united in morphofunctional zones (about 24 rosettes per zone, a total of 240-250 cells) formed from cambial cells of the same type and presenting a cell base of the system regulating proliferation and differentiation processes in the epithelium [4,5].…”
Section: Resultsmentioning
confidence: 99%
“…Rosettes, in turn, are united in morphofunctional zones (about 24 rosettes per zone, a total of 240-250 cells) formed from cambial cells of the same type and presenting a cell base of the system regulating proliferation and differentiation processes in the epithelium [4,5]. As soon as half of cambial cells starts mitosis, the release of the other half of these cells is inhibited, which leads to division of the zone into two parts or subunits with equal number (12) of cambial cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations